Addressing distress management challenges: Recommendations from the consensus panel of the American Psychosocial Oncology Society and the Association of Oncology Social Work. (24th May 2021) - Deshields, Teresa L.; Wells‐Di Gregorio, Sharla; Flowers, Stacy R.; Irwin, Kelly E.; Nipp, Ryan; Padgett, Lynne; Zebrack, Brad
Abstract: Distress management (DM) (screening and response) is an essential component of cancer care across the treatment trajectory. Effective DM has many benefits, including improving patients' quality of life; reducing distress, anxiety, and depression; contributing to medical cost offsets; and reducing emergency department visits and hospitalizations. Unfortunately, many distressed patients do not receive needed services. There are several multilevel barriers that represent key challenges to DM and affect its implementation. The Consolidated Framework for Implementation Research was used as an organizational structure to outline the barriers and facilitators to implementation of DM, including: 1) individual characteristics (individual patient characteristics with a focus on groups who may face unique barriers to distress screening and linkage to services), 2) intervention (unique aspects of DM intervention, including specific challenges in screening and psychosocial intervention, with recommendations for resolving these challenges), 3) processes for implementation of DM (modality and timing of screening, the challenge of triage for urgent needs, and incorporation of patient‐reported outcomes and quality measures), 4) organization—inner setting (the context of the clinic, hospital, or health care system); and 5) organization—outer setting (including reimbursement strategies and health‐care policy). Specific recommendations for evidence‐based strategies and interventions for each of the domains of the Consolidated Framework for Implementation Research are also included to address barriers and challenges.